Hubungan Perokok Pasif dengan Tingkat Kejadian Kanker Serviks di RSUD Dr Moewardi - Syahmi Amar; Rustam Sunaryo; Bhisma Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: Incidence of cervical cancer each year has increased and the risk of death from cervical cancer is also increased. Cigarette smoke is one of the risk factors associated with cervical cancer which contains chemicals such as nicotine and benzopiren. The content of these chemicals may increase the risk of cervical cancer by various mechanisms. The purpose of this study was to determine the incidence rate of cervical cancer associated with exposure to passive smokers is connected. Methods: This type of research is an case-control. Sample of this study were gynecologic cancer patients with a total sample of 60 people. Measuring instrument used was a validated questionnaire, and performed data analysis with multiple logistic regression analysis. Result: Found a statistically significant association between passive smoking with the incidence of cervical cancer. Passive smokers will have 11,5 ??times the cervical cancer than non-passive smokers (p=0,001, OR = 11,5). Conclusion: Based on studies of passive smoking women would run the risk of cervical cancer will have 11,5 times higher than non-passive smokers. Key words: passive smoker, cervical cancer